Transparency of human resource policy - Erik Mellander (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
The scope of public human resource policy is outlined. Motivation for the need of transparency in this policy is provided in terms of informational asymmetries, human capital externalities, and long planning horizons. Transparency is defined both along a time dimension - ex ante and ex post - and by a taxonomy due to Geraats (2014), referring to different facets of decision-making, implementation, and outcomes: political, economic, procedural, policy, and operational transparency. Five aspects on human resource policy relevant for transparency are considered: efficiency and equity, input utilization, learning outcomes, the dimensioning of education, and benefits and costs. Finally, suggestions for improved transparency are considered. These involve devoting resources to research on the measurement of human capital externalities, facilitation of ex ante benefit-cost analyses preceding human resource policy decisions, and strengthening of political accountability through intermediate follow-ups during policy implementation, combined with commitment of funds to finance independent evaluations of the policy's effects.
Keywords: I28; H11; H44; D62; D61; H83; 330; market failures; human capital externalities; long planning horizons; ex ante benefit-cost analyses; effect evaluations